⍺-WEAKLY GENERALIZED CONTINUOUS MAPPINGS IN INTUITIONISTIC FUZZY TOPOLOGICAL SPACES - N. Sangeetha, R. Krishna Moorthy, S. Meena piyadarshini (International Journal of Advanced Science and Technology, 2020)
In this paper we introduce and study the concepts of intuitionistic fuzzy a weakly generalized continuous mappings in intuitionistic fuzzy topological space. We investigate some of their properties.